Mechanical charaterization of S-glass and E-glass reinforced epoxy composite elbow pipe joints submerged in sea water - Bobba, Sujith (2019)
In many engineering applications composite pipes are generally used because of their high strength and stiffness, excellent fatigue and corrosion resistance. More than 70 percent of the world’s oil and gas transport pipelines are beyond 40 years old and there is a need to change them due to their gradual degradation in their operating environment.